Die Bromberger Bibliothek (Biblioteka Miejska w Bydgoszczy) w świetle referatu Goerga Minde-Poueta (Kronika Bydgoska, 2020)
The Municipal Library in Bydgoszcz was founded in 1903; it is one of the most recently established scientific libraries in Poland. Like many cultural and educational institutions from the region annexed by Prussia, it was a German initiative, which was intended to serve the German country and German community. The inside story of the library foundation and the first years of its activity are described in a report written by Georg Minde-Pouet, the first manager of the Municipal Library in Bydgoszcz, presented during the 51st Convention of German Philologists and Pedagogues in Poznan, held in October 3-6, 1911, and later printed in a collection of selected reports from the convention in 1911. The article analyzed in detail the report of G. Minde-Pouet. It emphasized the main themes expressed by the reporter/author: genesis of the library foundation; the origins of the library; library book collection; the principles of using the library collection. It also revealed the previously unknown circumstances of building the library collection. The report of G. Minde-Pouet was confronted with later studies concerning the library in Bydgoszcz. Reading of the report written more than a hundred years ago leads to new discoveries, to partial verification of knowledge on the Municipal Library in Bydgoszcz. It can and should be an inspiration to further research on this little-known and forgotten episode from its history.